Construction, validation and reliability of the family adaptation scale of adults with mental disorders - Mejía-Benavides, Jorge Emmanuel (Universidad de Sonora, 2019)
Introduction: Mental disorders are psychiatric disorders that are manifested by failures in the adaptation process and that are expressed by abnormal behavior, affecting both the person who has the illness and all members of his family. Objective: Design and validate an instrument to measure the adaptation of the family of adults with mental disorders. Methodology: The instrument was developed from the phases proposed by Sanchez and the questions were developed based on the Nursing Outcomes Classification (NOC) and on the literature review. The instrument was applied to 261 family members with a member with mental health problems from the northeastern part of the State of Guanajuato, Mexico. For the validity of the construct, factor extraction with principal components and Varimax rotation was performed with Eigen values above 1 and factorial load greater than .40. Results: The analysis showed six factors with an explained variance of 62.84%, while the Cronbach’s alpha reliability coefficient ranged between .62 and .83 for the dimensions and .84 on the total scale. Conclusion: The instrument showed that it is reliable and valid for measuring family adaptation.